Genomic distribution of SINEs in Entamoeba histolytica strains: implication for genotyping - Kumari, Vandana (BioMed Central, 2013)
BACKGROUND: The major clinical manifestations of Entamoeba histolytica infection include amebic colitis and liver abscess. However the majority of infections remain asymptomatic. Earlier reports have shown that some E. histolytica isolates are more virulent than others, suggesting that virulence may be linked to genotype. Here we have looked at the genomic distribution of the retrotransposable short interspersed nuclear elements EhSINE1 and EhSINE2. Due to their mobile nature, some EhSINE copies may occupy different genomic locations among isolates of E. histolytica possibly affecting adjacent gene expression; this variability in location can be exploited to differentiate strains. RESULTS: We have looked for EhSINE1- and EhSINE2-occupied loci in the genome sequence of Entamoeba histolytica HM-1:IMSS and searched for homologous loci in other strains to determine the insertion status of these elements. A total of 393 EhSINE1 and 119 EhSINE2 loci were analyzed in the available sequenced strains (Rahman, DS4-868, HM1:CA, KU48, KU50, KU27 and MS96-3382. Seventeen loci (13 EhSINE1 and 4 EhSINE2) were identified where a EhSINE1/EhSINE2 sequence was missing from the corresponding locus of other strains. Most of these loci were unoccupied in more than one strain. Some of the loci were analyzed experimentally for SINE occupancy using DNA from strain Rahman. These data helped to correctly assemble the nucleotide sequence at three loci in Rahman. SINE occupancy was also checked at these three loci in 7 other axenically cultivated E. histolytica strains and 16 clinical isolates. Each locus gave a single, specific amplicon with the primer sets used, making this a suitable method for strain typing. Based on presence/absence of SINE and amplification with locus-specific primers, the 23 strains could be divided into eleven genotypes. The results obtained by our method correlated with the data from other typing methods. We also report a bioinformatic analysis of EhSINE2 copies. CONCLUSIONS: Our results reveal several loci with extensive polymorphism of SINE occupancy among different strains of E. histolytica and prove the principle that the genomic distribution of SINEs is a valid method for typing of E. histolytica strains.